THE FUNCTION OF THE GOVERNMENT’S SYARIA BANK IN WEST JAVA - Firsanty, Farah Putri; Gunawan, Wahyu; Masyita, Dian; Setiawan, Maman (CosmoGov: Jurnal Ilmu Pemerintahan, 2026)
Banking is a key financial services sector that plays a vital role in both national and global economies. In Indonesia, the industry is divided into conventional and sharia banking. Sharia banking operates in accordance with the principles of the Quran and Hadith and is classified into three categories based on asset ownership: Sharia commercial banks, Sharia business units, and Sharia rural banks. In terms of ownership, these institutions include state-owned, government-owned, and private sharia banks. This study examines the functions of government-owned sharia banks in West Java using Robert K. Merton’s theory of structural functionalism, which identifies manifest, latent, dysfunctional, and non-functional roles within the banking ecosystem. The findings reveal that both manifest and latent functions are present in government-owned sharia banks in West Java. However, certain aspects require improvement to prevent dysfunction and non-function in operational performance. The study suggests that government-owned sharia banks should strengthen sharia financial literacy and inclusion among West Java’s population. Strengthening these aspects would foster the sharia economy and positively impact national development. This is significant as West Java ranked first in the 2025 Indonesia Muslim Travel Index (IMTI), reflecting its strong halal ecosystem linked to sharia banking.